Jamie Boulding. The Multiverse and Participatory Metaphysics: A Theological Exploration - Qureshi-Hurst, Emily ca. 20./21. Jh. (Philosophy, theology and the sciences, 2022)
Boulding, Jamie. The Multiverse and Participatory Metaphysics: A Theological Exploration, London: Routledge, 2021. 196 pp.